Calculating the flattening coefficient between roll gaps at the horizontal deflection of work rolls. (7th February 2019) - Bai, Z. H.; Xing, Y.; Liu, S. Y.; Li, B. Y.; Liu, Y. X.; Cui, Y. Y.
ABSTRACT: The market demand for high-quality cold-rolled strips has increased along with the rapid development of home appliance manufacturing, aviation and other fields. As the existing research has been largely ignored on the horizontal deflection of work rolls, this paper investigates the characteristics of the equipment and the processes of a slender rolling mill, and then proposes a model for calculating the flattening coefficient between roll gaps at the horizontal deflection of work rolls. A typical product of a 550 mill taken from a steel plant is used as an example, and the factors that affect the flattening coefficient between roll gaps, including the difference between the front and rear tension and the diameter of work rolls, are quantitatively analysed. This paper then proposes a forecasting software that can greatly strengthen the plate-shape controlling ability of rolling mills and improve their product quality, thereby the software deserves to be promoted.